2016
DOI: 10.1136/bmjopen-2016-012108
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological interventions to improve sleep in hospitalised adults: a systematic review

Abstract: ObjectivesPatients often suffer from disturbed sleep in hospital. Poor-quality sleep in hospitalised patients has been associated with significant morbidity and pharmacological sleep aids are often prescribed. The objective of this systematic review is to evaluate the comparative efficacy and safety of pharmacological interventions used for sleep in hospitalised patients.Setting/participantsWe searched MEDLINE, Embase, the Cochrane database and grey literature for prospective studies that evaluated sleep in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 45 publications
0
35
0
2
Order By: Relevance
“…Another reason that these findings should be interpreted with caution is related to the medication all participants were prescribed for the duration of this study. Sedation with drugs accelerates sleep onset, but there is no evidence that it improves sleep efficiency or quality (Kanji et al ., ). Antidepressant treatment by most selective serotonin reuptake inhibitors seems to reduce total sleep time and alter the pattern of dreams (Tribl et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Another reason that these findings should be interpreted with caution is related to the medication all participants were prescribed for the duration of this study. Sedation with drugs accelerates sleep onset, but there is no evidence that it improves sleep efficiency or quality (Kanji et al ., ). Antidepressant treatment by most selective serotonin reuptake inhibitors seems to reduce total sleep time and alter the pattern of dreams (Tribl et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…A recent systematic review concluded that there is insufficient evidence to suggest that pharmacotherapy improves the quality or quantity of sleep in hospitalized patients [ 36 ▪▪ ]. The following drugs, however, are recently being used to improve sleep in postoperative patients.…”
Section: Measures To Improve Postoperative Sleepmentioning
confidence: 99%
“…In hospitalised patients, sleep deprivation has been linked to poorer recovery and increased risk of delirium . Sedative–hypnotic medications are frequently prescribed in hospitals despite limited evidence for effectiveness in this setting, and contraindications such as high falls risk or cognitive impairment . Aside from the immediate risks, commencing sedative–hypnotic medications in hospital may also lead to longer‐term use in the community.…”
Section: Conflicts Of Interest Statementmentioning
confidence: 99%